Mesenchymal Hamartoma in Children: A Diagnostic Challenge - Muhammad Rehan Khan; Larry A. Binkovitz; Thomas C. Smyrk; D. Dean Potter; Katryn N. Furuya (Case Reports in Pediatrics)
Mesenchymal hamartoma is a benign tumor of the liver with a poorly understood pathogenesis. It is uncommon in older children, especially after 2 years of age. The signs and symptoms may be nonspecific; therefore, a high index of suspicion is required for diagnosis and treatment. We report a 5-year-old previously healthy male who presented with acute abdominal pain, fatigue, and fever. He was diagnosed with pneumonia initially and treated with antibiotics. A computed tomography (CT) scan done for evaluation of his persistent abdominal pain demonstrated a hepatic mass. Follow-up magnetic resonance imaging (MRI) of the liver demonstrated multiple serpiginous tubular-type structures, read as possible Caroli syndrome. He had a normal abdominal examination and normal biochemistries including alanine aminotransferase, aspartate aminotransferase, gamma-glutamyl transferase, alkaline phosphatase, and alpha-fetoprotein. He was referred to our institution for second opinion. On further review of his imaging studies, the lesion was thought to be a mesenchymal hamartoma. He subsequently underwent resection of the mass. Pathology confirmed the diagnosis of mesenchymal hamartoma.